2022
DOI: 10.1101/2022.10.25.513437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chinese fir genome and the evolution of gymnosperms

Abstract: Seed plants comprise angiosperms and gymnosperms. The latter includes gnetophytes, cycads, Ginkgo, and conifers. Conifers are distributed worldwide, with 630 species distributed across eight families and 70 genera. Their distinctiveness has triggered much debate on their origin, evolution, and phylogenetic placement among seed plants. To better understand the evolution of gymnosperms and their relation to other seed plants, we report here a high-quality genome sequence for a tree species, Chinese fir (Cunningh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 157 publications
0
12
0
Order By: Relevance
“…The application of exogenous GABA could effectively reduce ROS levels and modulate phytohormone cross-talk, thereby enhancing tolerance to multiple stresses [44]. Research by Lin et al showed that the exogenous application of astringent seed extracts could enhance the adaptability of Chinese fir seedlings to stressful high-aluminum conditions [11]. Here, the substantial accumulation of GABA in astringent seeds may play a role in this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of exogenous GABA could effectively reduce ROS levels and modulate phytohormone cross-talk, thereby enhancing tolerance to multiple stresses [44]. Research by Lin et al showed that the exogenous application of astringent seed extracts could enhance the adaptability of Chinese fir seedlings to stressful high-aluminum conditions [11]. Here, the substantial accumulation of GABA in astringent seeds may play a role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, extensive investigations have been conducted on the issue of astringent seeds in Chinese fir, including anatomical analysis [2,5] and identification of intrinsic components [6], physiological and biochemical changes [5,7,8], as well as ecological factors contributing to the production of astringent seeds [4,9,10]. Generally, the process of astringent seed formation can be divided into two stages: embryo abortion and astringent substance accumulation [11]. The process of astringent seed abortion seems to be closely related to the pollination process.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the insidious onset of liver cancer in most patients, HCC is often diagnosed at an advanced stage, resulting in poor prognostic outcomes [7,8] Hepatic artery infusion chemotherapy (HAIC) is an important treatment modality for advanced-stage liver cancer. However, the severe systemic toxicity of the rst-line chemotherapeutic agent oxaliplatin has led to poor tolerability in patients at this stage, resulting in forced discontinuation of treatment [9,10] . Therefore, there is an urgent need to develop alternative drugs that are safe, effective and have low toxicity, especially for patients with advanced liver cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin was found to be the rst metal-based anticancer agent, which was approved by the U.S. Food and Drug Administration (FDA) in 1978 [1]. It has been widely used as a rst-line chemotherapy drug for clinical treatment against various types of solid organ tumors when monotherapy or combination therapy with other compounds [2][3][4][5]. However, dose-dependent cardiotoxicity signi cantly increased the risk of cardiovascular complications including cardiomyopathy, hypertension, cardiac ischemia, and arrhythmias [6][7][8].…”
Section: Introductionmentioning
confidence: 99%